Access to Meighen Island, N.W.T. - MacKay, D.K.; Arnold, K.C. (ARCTIC, 1965)
Discusses the problem of access by light aircraft to the Polar Continental Shelf Project's icecap station on Meighen from Isachsen on Ellef Ringnes Island. Data are tabulated to show the incidence of poor visibility and other hazards at Meighen Island, and a calculation of probability indices for successful round-trip flights in different months and conditions is attempted. Warning is given that these low figures indicate that planning of work on Meighen should allow ample margin of time to cover delays due to unsuitable flying conditions.